Managerial Strategies of Religious Organizations in the Development of Islamic Education Institutions: A Study on Muhammadiyah and NU - Idwin, Muammar; Samad, Duski; Sutan Mamad, Firdaus (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research aims to examine and compare the roles of the two largest Islamic organizations in Indonesia, namely Muhammadiyah and Nahdlatul Ulama (NU), in the fields of Islamic education, socio-religion, and religious moderation. Through a literature study method and a qualitative-descriptive approach, this research reveals the ideological characteristics, education system, and socio-religious contributions of the two organizations in shaping a moderate Islamic society. Muhammadiyah is known for its modernist and rational approach to education development and its orientation towards the purification of Islamic teachings, while NU emphasizes traditional and cultural values in developing education and socio-religious practices. In the managerial context, Muhammadiyah adopts a strategy based on a structured and efficient institutional system, focusing on improving management quality, accountability, and developing a science and technology-based curriculum. Meanwhile, NU prioritizes cultural and participatory-based strategies through pesantren and informal education with strong traditional roots, as well as establishing active community involvement in the education process. The study results show that both organizations have significant contributions in strengthening religious moderation in Indonesia through distinctive yet complementary approaches. The collaboration of the values of modernity and traditionalism in the management of educational institutions is a strategic force in building an inclusive, adaptive and competitive Islamic education system.